Pengaruh Fear of Missing Out dan Kesepian terhadap Psychological Well-Being pada Remaja Akhir Pengguna Media Sosial Twitter di Jawa Barat - Prameswari, Tiara Puspita; Chotidjah, Sitti; Wyandini, Diah Zaleha (JURNAL PSIKOLOGI INSIGHT, 2022)
Abstract  This study aims to determine the effect of fear of missing out and loneliness on psychological well-being in late adolescents using Twitter in West Java. This study uses a quantitative method with a correlational design. The sample of this study consisted of 385 respondents with the characteristics of late adolescents with an age range of 15-19 years in West Java and actively using Twitter. The sampling technique used is accidental sampling. Researcher used the Fear of Missing Out Scale, the Loneliness Questionnaire, and Ryff's Psychological Well-Being Scale. The data analysis used was multiple linear regression analysis with a significance value of 0.001. Referring to the result of data analysis, it can be concluded that fear of missing out and loneliness affect psychological well-being and the influence given is quite large.Keywords: fear of missing out, loneliness, psychological well-being.Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh dari fear of missing out dan kesepian terhadap psychological well-being pada remaja akhir pengguna media sosial Twitter di Jawa Barat. Penelitian ini menggunakan metode kuantitatif dengan desain korelasional. Sampel penelitian ini terdiri atas 385 responden dengan karakteristik remaja akhir dengan rentang usia 15-19 tahun di Jawa Barat dan aktif menggunakan Twitter. Teknik sampling menggunakan accidental sampling. Peneliti menggunakan Fear of Missing Out Scale, Skala kesepian, dan Ryff’s Psychological Well-Being Scale. Analisis data yang digunakan adalah analisis regresi linear berganda dengan nilai signifikansi 0.001. Berdasarkan hasil analisis data, dapat disimpulkan bahwa fear of missing out and kesepian berpengaruh terhadap psychological well-being dengan pengaruh yang besar.Kata kunci: fear of missing out, kesepian, psychological well-being.